The influence of al-Rifā‘Iyyah tariqa on Dabus arts in Malay society - Mohd Zulhafizi Salim,; Wan Haslan Khairuddin,; Faudzinaim Badaruddin,; Nozira Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Malay community is a cultural and artistic society. Their arts and culture are highly civilized. This is due to Islamization. One of the Malay arts that are increasingly marginalized is the Dabus Dance. The art of Dabus Dance was formed through the influence of the al-Rifā‘iyyah tariqa. The two factors were the main problem of this paper. Therefore, the objective of this paper was to study the background of the al-Rifā‘iyyah tariqa and the Dabus Dance as well as to examine the influence of the al-Rifā‘iyyah tariqa on the Dabus Dance. To achieve the objectives, this paper used a qualitative approach that includes data collection, content analysis, historical analysis, and inductive and deductive methods. The findings included the background of the al-Rifā‘iyyah tariqa and the Dabus Dance as well as evidence of the al-Rifā‘iyyah tariqa’s influence on the Dabus art. This study implied and expected to reintroduce the art of Dabus Dance and al-Rifā‘iyyah tariqa.